Charity Box Based Camera and Security System Internet Of Things and Telegram - Imam Fahmi Udin Ma'ruf; Jamaaluddin; Izza Anshory (Universitas Muhammadiyah Sidoarjo, 2022)
Theft in a place of worship is a crime by stealing things that are not privately owned but public propertywithout permission and these activities are carried out from religious places such as mosques, churches andmonasteries. The theft of charity box funds is an interesting topic for some people and the mosque manager personallyin particular, considering that charity box funds are general funds intended for the renovation or purchase of mosqueneeds and the needs of religious events. By using a microcontroller as an auxiliary component to monitor valuables.This microcontroller control system can be used to secure charity box funds in any mosque equipped with a securityfeature based on Selenoid door locks that can only be opened by ESP 32-CAM and using a vibration sensor will detectshocks and a buzzer will sound. sounds like an alarm for Telegram to alert the Mosque management in the event ofthe forced destruction of the charity box. So, looking at the source of the problem and technological developments ashappened before, it is very appropriate to use them to reduce the rampant theft in mosques. Therefore researcherswill design a tool, namely a camera system and security for charity boxes based on the internet of things and telegrams.